2022
DOI: 10.2169/internalmedicine.8473-21
|View full text |Cite
|
Sign up to set email alerts
|

Synovitis-acne-pustulosis-hyperostosis-osteitis Syndrome with Bilateral Pleural Effusion

Abstract: Pleural effusion is a rare manifestation in synovitis-acne-pustulosis-hyperostosis-osteitis (SAPHO) syndrome, which is characterized by the presence of osteoarticular lesions and dermatological involvement. We herein report a 71-year-old man with pleural effusion resulting from SAPHO syndrome. He was successfully treated using corticosteroids and has experienced no recurrence for one year. We should consider SAPHO syndrome when encountering cases of anterior chest pain and pleural fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A recent study showed that SAPHO syndrome may cause pulmonary vasculitis, 28 which may be a reason for pulmonary artery stenosis. Moreover, other pulmonary manifestations, such as patchy shadows (32.8%), ground‐glass opacity (16.4%), and pleural thickening (13.4%), were not uncommon in SAPHO patients 29 . The etiology of brain and pulmonary manifestation within SAPHO syndrome is not understood.…”
Section: Extracutaneous/osteoarticular Manifestationsmentioning
confidence: 99%
“…A recent study showed that SAPHO syndrome may cause pulmonary vasculitis, 28 which may be a reason for pulmonary artery stenosis. Moreover, other pulmonary manifestations, such as patchy shadows (32.8%), ground‐glass opacity (16.4%), and pleural thickening (13.4%), were not uncommon in SAPHO patients 29 . The etiology of brain and pulmonary manifestation within SAPHO syndrome is not understood.…”
Section: Extracutaneous/osteoarticular Manifestationsmentioning
confidence: 99%